O processo cognitivo dos professores imigrantes digitais no período inicial da pandemia do Coronavírus - Zorzin, Daiana dos Reis (2022)
With the emergence of the coronavirus in 2020, major changes needed to be made in all sectors of social life. Teaching and learning had to be adapted to the technologies of remote teaching, and the pandemic highlighted the dilemma of the lack of using the technologies of remote teaching in schools and universities. The government of the state of São Paulo, following the recommendations of their health authorities, declared a quarantine. Many sectors of public service and private business had to be reorganized quickly, especially in the domain of education. All educational institutions, including the universities, had to adapt to a new and entirely unexpected scenario. This study examines be the variety of experiences and adaptations that occurred in the use of the teaching platform “Microsoft Teams” used in the remote teaching of the Catholic University of Sao Paulo from March 2020 on. Until 2020, Microsoft Teams had been a software for communication by videoconference without much relevance to academia. Nevertheless, it was chosen to give continuity to the teaching in all classes of all programs of the Catholic University of São Paulo. Without any previous preparation or training of the students and professors, the access and usability of this technology seemed to bring great problems in this situation. How would the generations of teachers and students deal with, and use, these new technologies?